Designing of the tank baffles damping liquid resilient oscillations in tanks - Синеглазов, В. М.; Кеменяш, Ю. М. (Proceedings of National Aviation University (archive), 1999)
Considered is designing of optimal form of tank baffler. It is shown that the efficiency of tank baffler can be increased by reducing their weight and changing their forms